Electricity and Natural Gas Prices Sharing the Long-term Trend: Some Evidence from the Spanish Market - Furio, Dolores; Poblacion, Javier (International Journal of Energy Economics and Policy, 2018)
The relationship between electricity prices and fuel costs has been extensively studied. Many studies have analyzed the relationship between electricity and natural gas prices and found that electricity and natural gas futures prices are cointegrated. In this paper, using different factor models to jointly estimate the dynamics of both commodities, we show that natural gas and electricity prices are not only cointegrated but also share common long-term dynamics. This finding has crucial implications in terms of managing and hedging the risk faced by utilities, because the common long-term trend finding implies that the spark spread risk reflects only short-term effects. Moreover, these results indicate that by using prices from both commodities, it is possible to extract more information for estimation purposes. Keywords: Stochastic Calculus, Natural Gas, Electricity JEL Classifications: C32, C51, C60, G13.